INTEGRASI NILAI-NILAI ISLAM DAN KEARIFAN LOKAL DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN BERBASIS KARAKTER - MUH IBNU SHOLEH; SOKIP SOKIP; ASROP SYAFI’I; MUH HABIBULLOH; SAHRI SAHRI; NUR ‘AZAH; FAKHRUDDIN AL FARISY (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2025)
The integration of Islamic values and local wisdom in the development of character-based education curricula is an important strategy in shaping a generation that excels academically, possesses noble morals, and is rooted in local culture. This study aims to analyze the integration of Islamic values and local wisdom in the development of character-based education curricula. The approach used is library research, which involves an in-depth review of relevant literature, including educational policy documents, books, and journal articles. The results of the study show that Islamic values such as honesty, responsibility, and mutual cooperation can align with local wisdom such as the tradition of deliberation and customs. The integration of both in the curriculum contributes to the formation of students' character, which is not only morally upright but also deeply rooted in local culture. This study recommends synergy between the government, educators, and the community in designing a contextual and applicable curriculum.